2017
DOI: 10.1016/j.jsps.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

High resolution UHPLC-MS characterization and isolation of main compounds from the antioxidant medicinal plant Parastrephia lucida (Meyen)

Abstract: High-resolution mass spectrometry is currently used to determine the mass of biologically active compounds in medicinal plants and food and UHPLC-Orbitrap is a relatively new technology that allows fast fingerprinting and metabolomics analysis. Forty-two metabolites including several phenolic acids, flavonoids, coumarines, tremetones and ent-clerodane diterpenes were accurately identified for the first time in the resin of the medicinal plant (Asteraceae) a Chilean native species, commonly called umatola, coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 33 publications
3
29
0
Order By: Relevance
“…The title compound was isolated using medium pressure column chromatography (MPCC) from Parastrephia quadrangularis, a medicinal plant used by the Aymara Amerindians [6,7], a known producer of several flavonoids and benzoic acid derivatives with antioxidant activity [8][9][10][11]. Following our program to isolate interesting metabolites from the Atacama Desert Flora, Northern Chile [12][13][14][15][16][17][18], dried aerial parts of P. quadrangularis (1622 g) collected in april 2015 in "El Tatio", Andean mountain range of the of Atacama Desert, II Region, Northern Chile, were defatted with hexane (3 liters, 3 times in the dark, 24 hours each time) and 54.82 g were obtained after evaporation of the solvent.…”
Section: Source Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The title compound was isolated using medium pressure column chromatography (MPCC) from Parastrephia quadrangularis, a medicinal plant used by the Aymara Amerindians [6,7], a known producer of several flavonoids and benzoic acid derivatives with antioxidant activity [8][9][10][11]. Following our program to isolate interesting metabolites from the Atacama Desert Flora, Northern Chile [12][13][14][15][16][17][18], dried aerial parts of P. quadrangularis (1622 g) collected in april 2015 in "El Tatio", Andean mountain range of the of Atacama Desert, II Region, Northern Chile, were defatted with hexane (3 liters, 3 times in the dark, 24 hours each time) and 54.82 g were obtained after evaporation of the solvent.…”
Section: Source Of Materialsmentioning
confidence: 99%
“…The title compound was isolated using medium pressure column chromatography (MPCC) from Parastrephia quadrangularis, a medicinal plant used by the Aymara Amerindians [6,7], a known producer of several flavonoids and benzoic acid derivatives with antioxidant activity [8][9][10][11] . These data, together with ESI-MS/MS and correlations observed in the HSQC and HMBC spectra, are consistent with the structure of the title compound (cf.…”
Section: Source Of Materialsmentioning
confidence: 99%
“…Another peak (5), at 17 min, 285 m / z , was present in DCM fractions and subextracts; this compound was identified as kaempferol, a flavonol also reported in P. lucida (Echiburu‐Chau et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Some phytochemical studies conducted in Parastrephia lucida identified 42 metabolites including several phenolic acids, flavonoids, coumarins, tremetones and entclerodane diterpenes (Echiburu‐Chau et al . ). Bohlmann et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation